Mahasiswi Kesejahteraan Sosial FISIP USU Ajak Anak-Anak Panti Tanamkan Rasa Percaya Diri Sejak Dini - Lestina Sitanggang; Bengkel Ginting (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Field Work Practice is one of the manifestations of students in implementing the knowledge that has been learned so far in the world of lectures. Field Work Practice aims to improve the skills of students in developing mindsets, adding ideas and insights so that later they produce a skilled and quality workforce. In addition, street vendors are one of the embodiments of the Tri Dharma of Higher Education, namely Service. Through this street vendor, it is hoped that students will be able to make a good contribution to society. Through this street vendor, the practitioner hopes that self-confidence can be built from an early age, because building self-confidence from an early age can have a good impact. Among them, being able to live his life in peace, always think positively and also of course will always be grateful for everything he goes through. Practitioners carry out street vendors using the casework method through their mini projects, namely instilling self-confidence from an early age with the stages of general or general intervention practice consisting of the assessment stage, program planning stage, intervention stage, evaluation stage, and termination stage. The purpose of this mini project is to achieve more life in the future